A 100‐V trench power MOSFET with taper‐shielded gate and non‐uniform drift region doping profile. Issue 6 (26th December 2022) - Deng, Gaoqaing; Wang, Jun; Tan, Chen; Wu, Yifan; Liang, Shiwei; Ng, Wai Tung
Abstract: A 100‐V Taper‐Shielded trench Gate (TSG) power metal‐oxide‐semiconductor field‐effect transistor (MOSFET) with superior figure‐of‐merit (FOM) is proposed and investigated in this paper. The gate of the proposed TSG‐MOSFET has a tapered shape to reduce the gate‐to‐drain overlap capacitance ( CGD ) and the gate charge ( Q G ). The vertical drift region doping profile of the proposed TSG‐MOSFET is enhanced in two ways. First is to use a multi‐step epitaxial growth to produce a non‐uniform doping profile. Second is to place a lightly doped n ‐region at the trench bottom. The bulk electric field in the blocking state can be more evenly distributed, allowing a shorter drift region and lower specific ON‐resistance ( R ON, sp ). Both technology computer‐aided design (TCAD) simulations and experiments were performed to evaluate the proposed device. The proposed device exhibits an improved R ON, sp of 27 mΩ·mm 2 with a breakdown voltage ( BV ) of 105 V. The third quadrant performance and the reverse recovery characteristics are also greatly improved. During reverse conduction, the amount of the excessive carriers stored in the drift region is reduced due to the shortened drift region and optimized drift region doping profile. The reverse recovery charge ( Q rr ) is decreased from 70 to 49 nC. When compared to its state‐of‐the‐art counterparts, the measured [ R ON  ×  Q G ] FOM and the Q rr showed a reduction of 23% and 28%, respectively. Abstract : A 100‐V TSG‐MOSFET with taper‐shaped gate and optimal drift region doping profile is proposed.The switching FOM, VF and Qrr is reduced by 23%, 13% and 33%, respectively, when compared to state‐of‐the‐art device with the same breakdown voltage.